2014
DOI: 10.3748/wjg.v20.i6.1626
|View full text |Cite
|
Sign up to set email alerts
|

Peritonitis with small bowel perforation caused by a fish bone in a healthy patient

Abstract: Perforation of the gastrointestinal tract by ingested foreign bodies is extremely rare in otherwise healthy patients, accounting for < 1% of cases. Accidentally ingested foreign bodies could cause small bowel perforation through a hernia sac, Meckel's diverticulum, or the appendix, all of which are uncommon. Despite their sharp ends and elongated shape, bowel perforation caused by ingested fish bones is rarely reported, particularly in patients without intestinal disease. We report a case of 57-year-old female… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
34
0
6

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(44 citation statements)
references
References 0 publications
1
34
0
6
Order By: Relevance
“…Accidental ingestion of fishbone is not uncommon but despite the sharp ends, the majority pass through the gastrointestinal tract uneventfully and perforation is rare. 1 They may on occasion, however, present in various ways from upper gastrointestinal impaction, dysphagia, bowel obstruction or silent perforation to frank peritonitis. The clinical history may not be helpful, and establishing the cause is difficult because the episode of swallowing the bone frequently goes unnoticed and may have occurred several days or weeks previously.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Accidental ingestion of fishbone is not uncommon but despite the sharp ends, the majority pass through the gastrointestinal tract uneventfully and perforation is rare. 1 They may on occasion, however, present in various ways from upper gastrointestinal impaction, dysphagia, bowel obstruction or silent perforation to frank peritonitis. The clinical history may not be helpful, and establishing the cause is difficult because the episode of swallowing the bone frequently goes unnoticed and may have occurred several days or weeks previously.…”
Section: Discussionmentioning
confidence: 99%
“…3 Most of these cases were described in fish eating countries (eg China) and no such cases have been reported in the UK. 1 Bhatia et al reported a case of terminal ileal perforation in an 85-year-old patient due to fish fin ingestion. 4 The patient was initially managed conservatively and, owing to worsening sepsis, needed laparotomy and terminal ileal enterotomy with removal of the offending FB.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3 Bones from sebastes, cod, sea bream, and eels are reported most often, [8][9][10][11] and these species are eaten in both Asian and European countries. In our case, the patient remembered eating fried sebastes 8 weeks earlier.…”
Section: Discussionmentioning
confidence: 99%
“…Одной из причин перфорации полых органов живота является попадание в просвет желудочно-кишечного тракта (ЖКТ) различных инородных тел (ИТ). По сведениям ряда авторов, этот вид перфорации встречается в практике хирурга крайне редко и чаще возникает у пациентов с грыженосительством или меккелевым дивертикулом [1,2].…”
Section: Introductionunclassified